ECONOMIC AND SOCIAL INFLUENCE ON HOUSEHOLD PRODUCERS IN LAMPUNG PROVINCE IN 2024 - Etika Revolusi Nusantari; I Wayan Suparta; Asih Murwiati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the influence of economic and social factors on household expenditure in Lampung Province using a quantile regression approach. The data used is from Susenas 2024, including the variables of per capita income, the education level of the head of household, and the area of residence. The results of the analysis show that the influence of the three variables is heterogeneous throughout the distribution of expenses. Per capita income has a negative and significant effect on the lower quantile, indicating a tendency to save or consume limited in low-income households. In contrast, education shows a positive and increasingly greater influence on the upper quantile, confirming the role of education in increasing consumption capacity. The area of residence also has a significant effect, where households in urban areas tend to have higher expenditures than rural areas. These findings confirm the importance of the quantile regression approach in understanding the dynamics of household consumption more comprehensively, as well as encouraging the formulation of more inclusive development policies based on local characteristics.